La asignación de servicios en los contratos de consorcios sin contabilidad independiente y su inafectación según la legislación del Impuesto General a las Ventas - Escalante Alpaca, Gonzalo Alonso (2019)
The non-taxation situation is a legal institution by which an economic act that does not comply with the tax incidence hypothesis is not subject to any tax burden regarding such act. This article analyzes the configuration of the non-taxation situation provided in subsection n) of article 2 of the Peruvian General Sales Tax Law regarding the allocation of services by the parties within a consortium contract without independent accounting in which one party performs as the operator of the contract.